Acoustic and durability performances of Arenga Pinnata panel - Ismail, Lindawati (2012)
This study aims to investigate the feasibility of Arenga Pinnata fiber to be applied for acoustical material component. There different binders namely polyurethane, urea formaldehyde and latex were employed as binder. The weight percentages of binder used were 10%, 15%, 20%, 25%, and 30%. Hand layup process was used in specimens production. The physical, acoustical and durability properties of the panels were investigated experimentally. The result shows that panel with high percentages of binder tends to have high density and tortuosity, but less porosity. The optimum porosity of 0.94 was obtained from panel that added with 10% Latex. In general, Arenga Pinnata panels show good sound absorption from mid to high frequency that is from 2000 Hz to 5000 Hz. The best sound absorption is performed by panel added with 10 % Latex with a maximum absorption coefficient (α) of 0.96 at 3000 Hz. The average Noise Reduction Coefficient (NRC) for all panels is 0.40. The value indicates that Arenga Pinnata panels are highly absorptive material. However, Arenga Pinnata panel is poor insulator since the optimum sound transmission loss (STL) is only 9.37 dB from panel added with 15% polyurethane at 5000 Hz. Thus, Arenga Pinnata panel is applicable to reduce echo caused by reflection effects within a room. Sound absorption increases as porosity increase and decrease as density-tortuosity increase. Hence, Arenga pinnata fiber is applicable for acoustical component panel. Moreover, Arenga Pinnata panels are durable that resist in water, heat, and fire. It is applicable for heat insulation